2016
DOI: 10.1128/mbio.00527-16
|View full text |Cite
|
Sign up to set email alerts
|

What’s in a Name? Species-Wide Whole-Genome Sequencing Resolves Invasive and Noninvasive Lineages of Salmonella enterica Serotype Paratyphi B

Abstract: For 100 years, it has been obvious that Salmonella enterica strains sharing the serotype with the formula 1,4,[5],12:b:1,2—now known as Paratyphi B—can cause diseases ranging from serious systemic infections to self-limiting gastroenteritis. Despite considerable predicted diversity between strains carrying the common Paratyphi B serotype, there remain few methods that subdivide the group into groups that are congruent with their disease phenotypes. Paratyphi B therefore represents one of the canonical examples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 42 publications
(53 reference statements)
6
47
1
Order By: Relevance
“…Unfortunately, preliminary tests showed that the SPAB_01124 marker was not able to specifically identify all the S. Paratyphi B tested. This result was not surprising with regards to the heterogeneous genomic background of this serotype, illustrated by the 10 PGs described by Connor et al ( 2016 ). Our investigations on the SPAB_01124 marker showed that it was absent in some of our S. Paratyphi B genomes and in the S. Paratyphi B genome ERR403703 belonging to the PG10.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Unfortunately, preliminary tests showed that the SPAB_01124 marker was not able to specifically identify all the S. Paratyphi B tested. This result was not surprising with regards to the heterogeneous genomic background of this serotype, illustrated by the 10 PGs described by Connor et al ( 2016 ). Our investigations on the SPAB_01124 marker showed that it was absent in some of our S. Paratyphi B genomes and in the S. Paratyphi B genome ERR403703 belonging to the PG10.…”
Section: Discussionsupporting
confidence: 59%
“…The WGS data were subsequently analyzed with Gegenees which is a software for comparative analysis of microbial WGS data, allowing to define genomic signatures unique for specified target groups. The contigs were exported to Gegenees (version 2.2.1; downloaded from http://www.gegenees.org ; Agren et al 2012 ) on a Linux platform with 16 S. Paratyphi B genomes (including 15 from Connor et al ( 2016 )) belonging to different PGs (two of each PG when possible) (Table 1 ) and 44 other genomes belonging to other frequent serotypes (Table 2 ), all publicly available on NCBI. The complete genomes mentioned in Tables 1 and 2 are annotated genomes which are preferably used as reference genomes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noticeably, this approach offers the highest genomic resolution possible and discriminatory power for even highly genetically close strains, which is lacking in conventional subtyping methods. In the last 5 years or so, the number of sequenced Salmonella genomes has been growing exponentially, largely due to the implementation of high-throughput genomic sequencing by the FDA (145), PulseNet International (146), the Wellcome Trust Sanger Centre (147), and Public Health England (148). As a result, WGS-based analysis is becoming the method of choice by public health laboratories for bacterial pathogen characterization and subtyping for epidemiological studies.…”
Section: Salmonella Typing Using Next-generation Sequencingmentioning
confidence: 99%
“…Paratyphi B (HG3) could be distinguished from S . Java (HG2) using two genes encoding Type III Secretion System (TTSS) effector proteins; sseJ and srfJ (10): with S . Paratyphi B possessing only srfJ but S .…”
Section: Introductionmentioning
confidence: 99%